"For the Eradication of Polish and Jewish-Muscovite Rule in Ukraine": An Examination of the Crimes of the Ukrainian Legion of Self-Defense. (4th December 2020) - Radchenko, Yuri; Usach, Andrii
Abstract: This study examines the German-sponsored Ukrainian Legion of Self-Defense (Ukrains'kyi Legion Samooborony, ULS), both its rank and file and its Ukrainian and German officers. Drawing upon sources in German, Ukrainian, American, and Israeli archives, the authors analyze the Legion's command structure, its relationship to the Third Reich, and its relationship to the Organization of Ukrainian Nationalists branch led by Andriy Atansovich Mel'nyk. The presentation of the political and military careers of lower-, mid-, and upper-level Legionnaires reveals their participation in killings of Jews, Poles, and other Ukrainians. The authors also identify the motivations of many of the actors. A close analysis of one case of German and Ukrainian "cooperation" in the Holocaust and other mass murders, this article relates to the debate over whether Holocaust perpetrators were "Ordinary Men."